Common Enemies at the Frontier of the Spanish Empire: Military Alliance between Pirates, African Americans and Native Americans in the Darién and Chocó regions. XVI - XVIII centuries. - Garzón Moreno, Daniel Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The present article aims to explore military alliance between pirates and corsairs, African Americans andNative Americans from the middle of the XVI century to the end of the XVIII century, in a border zone of the Spanish Empire formed by the Panama or Darien Isthmus. For the development of this research, it was essential to understand the internal dynamics of American piracy, Native Indians of the Caribbean and Paciic regions, African American slaves and marroons, and the Spanish authorities that exerted control in the Isthmus of Darién; a region which for more than two centuries confronted emerging military alliancesbetween the aforementioned agents, in order to hold their defense system and colonial domain in this border area. The multiplicity of factors that made possible an encounter or alliance among pirates, natives and negros in the American continent, whether for comercial, military or survival purposes, allows us to understand sociocultural phenomena developed in the New World, which gives evidence of forms of social relation that generated instability in the colonial order, with administrative, economic and military implications for the Spanish Empire.